Re-imagining ethical leadership as leadership for the greater good. Issue 2 (April 2017) - Wilson, Samuel; McCalman, James
Abstract: As Western nations slowly emerge from the recent global recession, there is demand among citizens for authorities to practice, and be seen to practice, ethical leadership. Although these conditions have been favourable for research into ethical leadership, extant research privileges westernized perspectives on ethical leadership and is largely silent on the meaning and practice of ethical leadership in the context of the 'big' ethical questions. In consequence, most research into ethical leadership, although well meaning, offers little guidance about how to imagine and implement sustainable, ethical solutions to systemic problems. In this research note, we outline a proposal to reimagine ethical leadership as leadership for the greater good and identify three avenues of research into leadership for the greater good that compliment existing critical perspectives on ethical leadership.